PENGARUH KEPUASAN KERJA, KEMAMPUAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SERBA USAHA TUNAS SETIA BARU PASURUAN - Ardiansyah, Vito; Dewi Andriani (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
The economy in Indonesia cannot be separated from the globalization that has swept the world recently. Without the support of reliable human resources, the company's activities will not be resolved properly. This shows that human resources are the main key that must be considered for all company needs. Through the efficient and effective use of human resources, companies can continue to compete to obtain the best results and achieve company goals. This research method uses quantitative methods, data collection is carried out using questionnaires. The sample used in this study was 60 respondents in employees of the Tunas Setia Baru Pasuruan All-Business Cooperative. The analysis used was a multiple linear regression analysis using the SPSS 22 program. This primary data is obtained through a questionnaire whose measurements use an interval scale that is tested for validity and reliability of the data is declared valid and reliable. The results of this study partially prove that job satisfaction affects employee performance, ability affects employee performance, and the work environment affects employee performance. And simultaneously job satisfaction, ability, and work environment affect employee performance in the all-business cooperative